Possible involvement of IGF‐1 signaling on compensatory growth of the infraspinatus muscle induced by the supraspinatus tendon detachment of rat shoulder. Issue 1 (13th January 2014) - Ichinose, Tsuyoshi; Lesmana, Ronny; Yamamoto, Atsushi; Kobayashi, Tsutomu; Shitara, Hitoshi; Shimoyama, Daisuke; Takatsuru, Yusuke; Iwasaki, Toshiharu; Shimokawa, Noriaki; Takagishi, Kenji; Koibuchi, Noriyuki
Abstract A rotator cuff tear (RCT) is a common musculoskeletal disorder among elderly people. RCT is often treated conservatively for functional compensation by the remaining muscles. However, the mode of such compensation after RCT has not yet been fully understood. Here, we used the RCT rat model to investigate the compensatory process in the remaining muscles. The involvement of insulin‐like growth factor 1 (IGF‐1)/Akt signaling which potentially contributes to the muscle growth was also examined. The RCT made by transecting the supraspinatus (SSP) tendon resulted in atrophy of the SSP muscle. The remaining infraspinatus (ISP) muscle weight increased rapidly after a transient decrease (3 days), which could be induced by posttraumatic immobilization. The IGF‐1 mRNA levels increased transiently at 7 days followed by a gradual increase thereafter in the ISP muscle, and those of IGF‐1 receptor mRNA significantly increased after 3 days. IGF‐1 protein levels biphasically increased (3 and 14 days), then gradually decreased thereafter. The IGF‐1 protein levels tended to show a negative correlation with IGF‐1 mRNA levels. These levels also showed a negative correlation with the ISP muscle weight, indicating that the increase in IGF‐1 secretion may contribute to the ISP muscle growth. The pAkt/Akt protein ratio decreased transiently by 14 days, but recovered later. The IGF‐1 protein levels were negatively correlated with the pAkt/Akt ratio. These results indicate that transection of the SSP tendon activates IGF‐1/Akt signaling in the remaining ISP muscle for structural compensation. Thus, the remaining muscles after RCT can be a target for rehabilitation through the activation of IGF‐1/Akt signaling.